Sprawozdanie z działalności Komitetu Nauk Teologicznych PAN w latach 2012–2019 - Porada, Rajmund; Anderwald, Andrzej (Studia Nauk Teologicznych PAN, 2021)
Sprawozdanie z działalności Komitetu Nauk Teologicznych PAN w latach 2012–2019